PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PEMBENTUKAN KARAKTER KEPEMIMPINAN SISWA SDN 2 BAJUGAN: Kuantitatif Quasi Experimental - Oktafia; Hamna; Mustakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation and influence of the Discovery Learning model on the development of leadership character among fourth-grade students at SDN 2 Bajugan. The research employed a quantitative method with a quasi-experimental design. The subjects consisted of class IV A students as the experimental group, who were taught using the Discovery Learning model, and class IV B students as the control group, who received conventional learning. Data were collected through observation, field notes, and pre-test and post-test assessments to measure leadership character. The findings indicated that the application of Discovery Learning in the experimental class did not produce statistically significant effects on students’ leadership character. However, the Wilcoxon Signed Ranks Test results showed p-values of 0.006 in the control group and 0.005 in the experimental group, both lower than 0.05, indicating significant differences between pre-test and post-test scores in both groups. The improvement in leadership character was greater in the experimental group than in the control group. In the experimental class, 15 out of 18 students showed progress, with a higher mean rank (10.03) compared to the control group (9.57). The absolute Z value in the experimental group (-2.834) was also higher than in the control group (-2.727), suggesting a stronger effect. In conclusion, the Discovery Learning model can effectively foster leadership character when designed with activities that encourage students’ active participation. This discovery-based learning process provides opportunities for students to take initiative, develop responsibility, and practice decision-making.